Model Oranjekapel. Vervanging van grote kerken door kleine - Steensma, Regnerus (Jaarboek voor liturgieonderzoek, 1992)
During the last thirty years in the Netherlands many parishes have much diminished in members and there has also been a decline in church attendance, both symptoms caused by secularization, shifts in living areas and changes in the church practice. The consequence of this is that many church buildings are becoming too large and in proportion to the small amount of churchgoers too expensive in maintenance and heating. This symptom occurs in particular in the old quarters of the big towns. The three commonest solutions to this problem are: sell the building or demolish it without replacement, make the existing building smaller or demolition and have it replaced by a smaller building. The disadvantage of the first solution is that the parish has no centre anymore and in actual practice often disappears and the drawback of the second solution is that there remains a large building with a great deal of maintenance. Both disadvantages are avoided in the third solution and besides the new church building has been adapted to the current wishes, not only as to the proportions but also as to the design of the building. Of the twenty-one torn-down churches from this study nine of them go back to the nineteenth or the early twentieth century, six of them date from the period between 1918 and 1940 and six of them go back to the fifties. The new small churches were built in the period 1974 to 1991, partly as independent buildings (12), partly equipped in a flat, a home for the elderly or an office-block. ...